2017
DOI: 10.1136/bmj.j3448
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome at 2 years for preterm children born at 22 to 34 weeks’ gestation in France in 2011: EPIPAGE-2 cohort study

Abstract: Objectives To describe neurodevelopmental outcomes at 2 years corrected age for children born alive at 22-26, 27-31, and 32-34 weeks’ gestation in 2011, and to evaluate changes since 1997. Design Population based cohort studies, EPIPAGE and EPIPAGE-2. Setting France. Participants 5567 neonates born alive in 2011 at 22-34 completed weeks’ gestation, with 4199 survivors at 2 years corrected age included in follow-up. Comparison of outcomes reported for 3334 (1997) and 2418 (2011) neonates born alive in the nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
269
4
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 346 publications
(303 citation statements)
references
References 64 publications
14
269
4
3
Order By: Relevance
“…35 Similarly, a study of 2901 livebirths at 22-32 completed weeks' gestation in 1997 in France, reported that at 5-years of age 14% of the children had moderate to severe disability and 25% had minor disability. Specialized health-care resources were used by 34% of the children born prematurely, compared with only 16% in a reference group of children born at 39-40 weeks.…”
mentioning
confidence: 99%
“…35 Similarly, a study of 2901 livebirths at 22-32 completed weeks' gestation in 1997 in France, reported that at 5-years of age 14% of the children had moderate to severe disability and 25% had minor disability. Specialized health-care resources were used by 34% of the children born prematurely, compared with only 16% in a reference group of children born at 39-40 weeks.…”
mentioning
confidence: 99%
“…The sample was recruited between 1985 and 1986, and thus replications with more recent samples are necessary, given that with improvements in neonatal care, survival of preterm infants has substantially improved over the past decades. Nevertheless, in general, the long‐term neurodevelopmental outcomes after preterm birth appear to be comparable, even in more recent samples (Cheong et al, ; Pierrat et al, ; Wolke, Strauss, et al, ). Despite the exceptionally good fit of the data to the model in the current study, it only explained a small amount of variance.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, rates were as high as 90 per cent in the Haute‐Normandie region. A recent EPIPAGE 2 benchmarking study in several regions in France observed that the rate of CP in Haute‐Normandie (2/87; 2.1%; range: 0.2%–7.7%]) was half that in France overall (4.6%; 95% CI: 3.9–5.5) …”
Section: Neuroprotective Effects Of Magnesium Sulphate In Clinical Obmentioning
confidence: 99%
“…Since 1980, the rate of CP in children born preterm has declined in Europe . In France the rate of CP decreased from 9 per cent in children born very preterm in 1997 to 5.4 per cent in 2011 …”
mentioning
confidence: 99%
See 1 more Smart Citation